Long‐term culture change related to rapid response system implementation. Issue 12 (December 2014) - Stevens, Jennifer; Johansson, Anna; Lennes, Inga; Hsu, Douglas; Tess, Anjala; Howell, Michael
<x xml:space="preserve">Abstract</x> Objectives Increasing attention to patient safety in training hospitals may come at the expense of trainee autonomy and professional growth. This study sought to examine changes in medical trainees' self‐reported behaviour after the institution‐wide implementation of a rapid response system. Methods We conducted a two‐point cross‐sectional survey of medical trainees in 2006, during the implementation of a rapid response system, and in 2010, in a single academic medical centre. A novel instrument was used to measure trainee likelihood of calling for supervisory assistance, perception of autonomy, and comfort in managing decompensating patients. Non‐parametric tests to assess for change were used and year of training was evaluated as an effect modifier. Results Response rates were 38% in 2006 and 70% in 2010. After 5 years of the full implementation of the rapid response system, residents were significantly more likely to report calling their attending physicians for assistance (rising from 40% to 65% of relevant situations; p < 0.0001). Year of training was a significant effect modifier. Interns felt significantly more comfortable in managing acutely ill patients; juniors and seniors felt significantly less concerned about their autonomy at 5 years after the implementation of the rapid response system. These changes were mirrored in the actual use of the rapid response system, which increased by 41% during the 5‐year period after adjustment for patient volume (p < 0.0001). Conclusions A primary team‐focused implementation of a rapid response system was associated with durable changes in resident physicians' reported behaviour, including increased comfort with involving more experienced physicians and managing unstable patients.